Macronutrients, vitamins, minerals and bioactive compounds in fresh and dehydrated basil (Ocimum basilicum) and its hot and cold infusions (Acta Scientiarum. Technology, 2021)
Basil (Ocimum basilicum L.) is one of the most popular plants cultivated worldwide. It is a good source of natural antioxidants and contains significant amounts of important phytochemicals. Thus, this study aimed to evaluate the macronutrients, minerals, vitamins and bioactive compounds of fresh and dehydrated basil and its hot and cold infusions. The basil presented high moisture (94.12%) and low lipid (0.20%), carbohydrates (5.25%) and dietary fibers (2.33%) content. There was no difference in vitamin C concentrations, total phenolics and antioxidant capacity between fresh and dehydrated basil and between the hot and cold infusions (p > 0.05). Potassium and calcium were the most prevalent minerals in dehydrated basil. The consumption of basil, especially in dehydrated form, can contribute significantly to the daily intake of minerals, vitamins C and E, and infusions are not a relevant choice of consumption to achieve nutritional recommendations.